Ответ:
6х-у=-1
2х-3у=-11 |*(-3)
-6х+9у=33
8у=32
у=4
6х-4=-1
х=0.5
Ответ:0,5;4
Пошаговое объяснение:
6x-y= -1,
2x-3y=-11
У=6х+1
2х-3(6х+1)= -11
2х-18х-3=-11
-16х=-11+3
-16х= -8
Х=0,5
х=0,5
У=6*0,5+1=4
У=4
Твой ответ
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
6х-у=-1
2х-3у=-11 |*(-3)
6х-у=-1
-6х+9у=33
8у=32
у=4
6х-4=-1
х=0.5
Ответ:0,5;4
Пошаговое объяснение:
Ответ:
6x-y= -1,
2x-3y=-11
У=6х+1
2х-3(6х+1)= -11
2х-18х-3=-11
-16х=-11+3
-16х= -8
Х=0,5
х=0,5
У=6х+1
Х=0,5
У=6*0,5+1=4
Х=0,5
У=4
Твой ответ
Пошаговое объяснение: